Evaluation of Educator Development Program in Improving the Performance of Madrasah Aliyah Teachers in Bengkulu - Zaleha Ismail; Shafinar Ismail; Khairiah Khairiah (Al-Khair Journal: Management Education, 2024)
Abstract: The purpose of this paper is to evaluate and analyze the educator development program in improving teacher performance. Using descriptive qualitative method with CIPP (Contex, Input, Process, Product) approach. Data sources are obtained from various sources both print and online media, scientific books, scientific articles both nationally and internationally. The results of the study can be concluded that the educator development program has been carried out quite well, but at the contex level teacher performance problems such as professionalism, mastery of technology are still weak, and teachers are less able to meet the demands of global competence, at the input level 20% of teachers teach not according to their fields, 20% are unable to plan learning programs, 40% of evaluations are not in accordance with the plans that have been prepared, the budget is still limited, and the books and information technology facilities are still uneven. Third, the process of implementing the development program is quite good. However, there are times when development is not carried out transparently, meaning that teacher needs are announced and those who have the ability can apply, causing teachers who are plotted to be non-linear, there are still teachers who have not been able to show good performance, due to budget constraints. Fourth, the product of the educator development program in general has been quite good, teachers already have a fairly good responsive, tenggon and trengginas character, but there are still teachers who are not innovative, and teachers still have difficulty improving their performance. So it can be suggested, to improve teacher performance, increase the evaluation of the teacher development program at Madrasah Aliyah. Keywords: Evaluation, Educator Development Program, Teacher Performance, Madrasah Aliyah Abstrak: Tujuan penulisan ini untuk mengevaluasi dan menganalisis program pengembangan tenaga pendidik dalam meningkatkan kinerja guru. Menggunakan metode kualitatif deskriptif dengan pendekatan CIPP (Contex, Input, Proses, Produk). Sumber data diperoleh dari berbagai sumber baik media cetak maupun media online, buku-buku ilmiah, artikel ilmiah baik nasional maupun internasional. Hasil penelitian dapat disimpulkan bahwa program pengembangan tenaga pendidik telah dilakukan cukup baik, namun pada tingkat contex permasalahan kinerja guru seperti profesionalitas, penguasaan teknologi masih lemah, dan guru kurang mampu memenuhi tuntutan kompetensi global, tingkat input 20% guru mengajar tidak sesuai bidangnya, 20% tidak mampu merencanakan program pembelajaran, 40% evaluasi tidak sesuai dengan rencana yang telah disusun, anggaran masih terbatas, dan fasilitas buku-buku dan teknologi informasi masih tidak merata. Ketiga, Proses pelaksanaan program pengembangan sudah cukup baik. Namun ada kalanya pengembangan dilakukan secara tidak transparan, maksudnya kebutuhan guru diumumkan dan yang mempunyai kemampuan boleh mengajukan, sehingga menyebabkan guru yang diplot tidak linier, masih terdapat guru belum mampu menunjukkan kinerja baik, karena keterbatasan anggaran. Keempat, Produk program pengembangan tenaga pendidik secara umum telah cukup baik, guru telah memiliki karakter tanggap, tenggon dan trengginas yang cukup baik, namun masih terdapat guru yang tidak inovatif, dan guru masih kesulitan meningkatkan kinerjanya. Sehingga dapat disarankan, untuk meningkatkan kinerja guru maka tingkatkanlah evaluasi terhadap program pengembangan guru pada Madrasah Aliyah. Kata Kunci: Evaluasi, Program Pengembangan Tenaga Pendidik, Kinerja Guru, Madrasah Aliyah